Social dominance orientation, intergroup contact and belief in traditional school culture as predictors for parents’ attitudes to school segregation in the Czech Republic - Cada, Karel; Gheorghiev, Olga (Frontiers in Psychology, 2023)
Background The over-representation of Roma children in segregated schools is well documented as a prevalent form of institutional racism in the Czech Republic. In the paper, we examine the inclination of parents to support school segregation. Objective The paper looks at parents’ preference for school segregation and explores its association to social dominance orientation, intergroup contacts, belief in traditional schooling and the absence of Roma children in school as proof of the school’s good quality. The first hypothesis examines an association between parents’ preference to withdraw their children from ethnically diverse schools and social dominance orientation (one’s degree of preference for inequality among social groups). The second one tests the belief in traditional schooling as a factor contributing to a preference for ethnically motivated withdrawal. The third one studies the extent to which parents’ preference to withdraw their children from ethnically diverse schools is affected by contact with Roma in their everyday life. The final hypothesis tests if parents who view Roma students as an indicator of poor education in a given school are more likely to oppose the presence of Roma students among their children’s peers. Methods Quantitative data collection was carried out on a sample of 1,803 respondents. The target group were families with at least one child of primary school age (6–14 years). A binary logistic regression analysis was implemented to assess these relationships. Results The study confirmed that ethnically motivated school withdrawal is associated with social dominance orientation, belief in traditional school culture and education. On the other hand, the role of inter-group contact in a school environment was not proved. However, the final statistical model was rather weak explaining approximately 9% of variance in segregation endorsement. The model fit improved significantly when an additional variable – absence of Roma as a sign of a good school – was added. Approximately 15% of the variance in segregation endorsement was explained by the modified set of predictors. Conclusion The study argues that ethnically motivated school withdrawal is a result of individual attitudes and situational factors. This means that researchers interested in informal school segregation will need to consider both groups of factors.